Advances in Silage Production and Utilization - da Silva, Thiago; Mauro Santos, Edson (IntechOpen, 2016)
Ensiling is a technique that is used to store food, mainly vegetable crops, to feed the herd when the forage supply from the pastures is not enough to maintain the productive performance of the ruminant animals. However, silage can also be used as substrate for biogas production and other different purposes. In the past years, we have seen many advances in the knowledge about silage production utilization, and this book is a compilation and discussion of the outstanding scientific research activities concerning actually the most recent advances and technologies that have been studied about silage and future demands. It is directed to a broad public of readers - farmers, academics, students, or anyone just curious or interested in the subject.